The use of cangrelor with heparin for left ventricular assist device implantation in a patient with acute heparin-induced thrombocytopenia - Yan K. Gernhofer (Journal of Cardiothoracic Surgery, 2018)
Abstract Background Optimal anticoagulation strategy for cardiopulmonary bypass (CPB) in end-stage heart failure patients with heparin-induced thrombocytopenia (HIT) requiring left ventricular assist device (LVAD) implantation remains uncertain. Presently, there are no large-scale randomized studies comparing outcomes of alternative anticoagulation strategies for CPB in this patient population. A novel antiplatelet agent – cangrelor, which is a potent P2Y12 inhibitor with robust antiplatelet efficacy, rapid reversibility, and measurable drug effect, has become available since 2015. Intraoperative anticoagulation for CPB using cangrelor with heparin has not been reported before. Case presentation We report the case of a 47-year-old male with ischemic cardiomyopathy and acute HIT, who underwent an urgent LVAD implantation using cangrelor with heparin for anticoagulation on CPB. This novel strategy resulted in satisfactory anticoagulation for CPB without perioperative thromboembolic events or major bleeding requiring reoperation. Conclusions Cangrelor with heparin was an effective anticoagulation strategy for CPB in this critically ill patient with acute HIT requiring an urgent LVAD implantation. Further studies are warranted to evaluate its efficacy and replicability in other patients with acute or subacute HIT who require urgent cardiac surgery.